Peran Hukum Internasional dalam Memerangi Perdagangan Manusia: Tinjauan Studi Literatur - Deri Wicaksono Surya; Tubagus Krisna Bayu (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Human trafficking is a serious challenge in the modern world and requires serious attention from the international community. This article discusses the role of international law in efforts to combat human trafficking through a review of literature studies. By analyzing various previous studies and related reports, this article investigates how international law has developed to address the problem of human trafficking. Through a literature study, this article identifies various international legal approaches that have been taken to address human trafficking as well as evaluates the effectiveness of measures and the challenges faced by the international community in combating human trafficking. The results of this literature review provide an understanding of the international legal landscape regarding human trafficking, as well as identifying areas where further efforts are needed. This article concludes the importance of interstate cooperation and effective legal implementation in efforts to effectively combat human trafficking throughout the world.